RESPONS SISWA TERHADAP LKPD BERBANTUAN MEDIA GAMBAR PADA PEMBELAJARAN MENULIS DESKRIPSI - Muhamad Anwar Latif; Ika Mustika; Reka Yuda Mahardika (IKIP Siliwangi, 2023)
Descriptive text learning is studied at the junior high school level, especially class VII, which is still not optimal because learning activities are still less popular with students and do not utilize technology so that students only use textbooks and student worksheet materials which are not interesting. This is due to limited facilities and infrastructure in schools, so learning innovation through practical and simple applications is needed. Thus, researchers tried to use LKPD assisted by image media to overcome this problem. The aim of conducting this research is to see how students respond to the use of LKPD assisted by image media in learning descriptive text. The research method used is quantitative descriptive with an instrument in the form of a questionnaire. Based on the research results, it is known that the results of the distribution of questionnaires, questions with a (+) character obtained a result of 90.6% with very good criteria and questionnaire questions with a (-) character obtained a result of 33.2 with good criteria. Thus, it can be concluded that the student response to the use of LKPD assisted by image media in learning descriptive text for class VIII students at SMP Negeri 2 Cimahi in this research is included in the very good category.